PULSE WAVE VELOCITY AS A NOVEL RISK FACTOR FOR CHRONIC KIDNEY DISEASE PROGRESSION - I. T. Murkamilov; K. A. Aitbaev; F. A. Yusupov (Кардиоваскулярная терапия и профилактика)
The roles of arterial stiffness and pulse wave velocity are considered, in progression cardiovascular and renal diseases. The influence of various treatment regimens is discussed, on arterial stiffness in cardiological patients with renal dysfunction.